Resíduos de agrotóxicos em alimentos no Paraná: um estudo acerca do monitoramento do PARA/PR (2001-2019). e2322251 - Shaiane Carla Gaboardi; Luciano Zanetti Pessôa Candiotto (Terr@ Plural, 2023)
In Brazil, the National Health Surveillance Agency (ANVISA) created the Program for Analysis of Pesticide Residues in Food (PARA) in 2001 with the purpose of evaluating pesticide residue levels reaching the consumer’s table. Currently, all Brazilian states participate in this program, except for Paraná, which established its own program in 2011 and ceased to participate in ANVISA’s analyses in 2016. In this context, this article aimed to analyze the results of pesticide residue monitoring in food in the state of Paraná and discuss the advances and limitations within the state program. The methodology relied on exploratory documentary research, analyzing reports from the Program for Analysis of Pesticide Residues in Food coordinated by ANVISA and the State Program for Analysis of Pesticide Residues in Food (PARA/PR), made available on the website of the Paraná State Health Department (SESA/PR). Additionally, bulletins and reports from the Surveillance and Health Care Plan for Populations Exposed to Pesticides in the State of Paraná (PEVASPEA) were also examined. It was identified that, on average, 60% of food samples analyzed in Paraná between 2001-2019 contained some level of pesticide contamination. The most frequently detected irregularities were found in samples of bell peppers, strawberries, cucumbers, and grapes. There are indications of multiple exposures, as some foods, such as strawberries, presented an average detection of up to eight different active ingredients per sample. The mos detected pesticides belong to the dithiocarbamate group, as well as carbendazim, imidacloprid, and tebuconazole. Thus, this study intends to raise awareness about the essential need to consider and demand less harmful methods for the environment and human health in food production, while promoting strategies for proper nutrition